Evaluating the possibilities of obtaining initial concentrates of rare earth elements (REEs) from fly ashes - J. Całus Moszko; B. Białecka; M. Cempa-Balewicz; H. Świnder (Metalurgija, 2016)
The article presents the results of initial laboratory research into the possibilities of obtaining REE from fly ash from one of Polish powerhouses. In the work the authors have presented the results of investigations into the obtaining of initial REEs concentrations from fly ashes by physicochemical and hydrometallurgical methods. These investigations provide a basis for developing a technology of RRE recovery from fly ashes produced in the process of hard coals combustion.